Pemanfaatan Limbah Peternakan Menjadi Biogas di Desa Sabrang, Kecamatan Ambulu, Kabupaten Jember - Kartini, Audiananti Meganandi; Fitria, Firda Lutfiatul; Pramitasari, Noven; Al Banna, Hasan; Purnagusti, Yangga; Pambudi, Junan Cahyo; Wicaksono, Ega Fajar (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
Sabrang Village is one of the villages in Ambulu sub-district, Jember Regency, the majority of the population make a living as farmers and ranchers.  Animals that are farmed are cows. Manure waste from cattle in Sabrang Village has not been managed and utilized properly, so if it can be managed properly, it will be able to improve the welfare of the people in the village.  This is in line with the Community Service Team program on livestock waste management and treatment to reduce environmental pollution. One that supports this program is to process livestock manure waste into something useful, one of which is an alternative fuel such as biogas. Therefore, it is necessary to increase public insight into the utilization of livestock manure waste into biogas.  This can later meet people's needs for fuel that will be useful for their lives later.